KENOTYPES OF BALKAR POETRY AND MECHANISMS OF THEIR FORMATION - K. K. BAUAEV (Кавказология)
The article highlights an important evolutionary period of national literature – the second half of the 60s – 70s of the last century. The author touches upon the problem of finding promising ways to develop the aesthetic consciousness of the people at the stage of transition from traditional reflective models based on folklore ideas and archetypes of ethnic thinking to the structures of a new formation. It is suggested that the appearance of a special type of images and their transition into cross-cutting symbols, and then into kenotypes, in these years is the result of a purposeful search for stable style-forming constructs in the process of overcoming the boundaries of established apperceptive models. The article identifies two main types of Balkar poetry kenotypes – reformational ones, created on the basis of ethnic archetypes, and autonomous ones, built within the framework of an"intertextual refrain". The author of the article considers the mechanism of formation of kenotypes to be the same for both types, which is convincingly justified by him on the examples of the works of famous Balkar poets -K. Sh. Kuliyev and T. M. Zumakulova.